Conflict Management between Communities and Mining Companies in the Social Resilience Perspective - Rijal Asnawi; Zaenal Fanani; Abdullah Said (Sekolah Pascasarjana Universitas Brawijaya, 2020)
This study aims to analyze the conflict management model in a comprehensive and detailed manner are as follows; (1) Analyzing conflicts between communities and mining companies; (2) What is the model of conflict management between communities and mining companies from the perspective of social security. Using a qualitative approach, and an Interactive Model analysis of Miles and Huberman, conclusions are obtained: First, Conflicts between communities and mining companies, such as (a), the existence of conflicts in the form of ongoing demonstrations; (b), the type of conflict in the form of conflict between social classes and political conflicts; (c) the causes of conflicts in the form of inadequate socialization, lack of disclosure of information on Mining Management, Differences of Interest, The existence of impacts in the form of loss and reduction of community production land and environmental damage as well as unresolved Impact Compensation. Second, Conflict Management Model viz. (a) conflict management style uses competition conflict management style and avoidance conflict management style, (b), the pattern of conflict management approach that is negotiation, mediation and conciliation which has not been effective so that it needs an arbitration step in conflict resolution.